INTENSIFIKASI PEMUNGUTAN PAJAK REKLAME DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN INDRAGIRI HULU TAHUN 2015-2016 - Ardeka Dwi Putra; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Regional Tax is one of the most important revenue for the Region, and Regional Tax also aims to increase prosperity and prosperity of the people of the region. The purpose of this study is to provide an overview of the intensification of advertisement tax collection in the District Revenue Service (DISPENDA) Indragiri Hulu. And to find out how far the contribution of advertisement tax to PAD in Indragiri Hulu regency.To achieve the purpose of this study, the type of research used is descriptive qualitative ie to provide a clear picture of the problems studied, interpret and explain the data systematically on the Revenue Service The area (DISPENDA) of Indragiri Hulu Regency with the research approach used is qualitative, that is to interview the respondent which contains questions about matters relating to the research problem. To measure the intensification of advertisement tax collecting is to see the level of taxpayer compliance as measured through the juridical aspect and psychological aspects. Juridical aspects consist of WP registration, SPOP reporting, tax calculation and tax payments. Psychological aspect consists of Counseling, Services, Inspection, Collection and Supervision. From the result of research indicate that intensification of advertisement taxation at Local Revenue Service (DISPENDA) of Indragiri Hulu Regency has been running well enough, or in other words intensification of tax bill advertisement run quite effective because every year there is an increase of tax payer by Taxpayer and obligatory amount the tax increases every year. Increased tax revenue is one indication of the increase in awareness of Taxpayers. But let the intensification can be improved for the purpose of the organization that is to increase tax revenue can be met. Then the contribution of advertisement tax to PAD in Indragiri Hulu regency is potential to be improved because the level of advertisement advertisement tax revenue every year is good because the trend is increasing as well as the increasing number of objects of advertisement tax which can still continue to be improved. Keywords: Tax Collection Intensification, Advertisement Tax Contributions, PAD.